APOE genotype and sex modulate Alzheimer’s disease pathology in aged EFAD transgenic mice - Balu, Deebika; Valencia-Olvera, Ana C.; Islam, Zarak; Mielczarek, Clare; Hansen, Allison; Perez Ramos, Tamara M.; York, Jason; LaDu, Mary Jo; Tai, Leon M. (Frontiers in Aging Neuroscience, 2023)
Increasing evidence supports that age, APOE and sex interact to modulate Alzheimer's disease (AD) risk, however the underlying pathways are unclear. One way that AD risk factors may modulate cognition is by impacting amyloid beta (Ab) accumulation as plaques, and/or neuroinflammation Therefore, the goal of the present study was to evaluate the extent to which age, APOE and sex modulate Ab pathology, neuroinflammation and behavior in vivo. To achieve this goal, we utilized the EFAD mice, which express human APOE3 or APOE4 and have five familial AD mutations (FAD) that result in Aβ42 overproduction. We assessed Aβ levels, reactive glia and Morris water maze performance in 6-, 10-, 14-and 18-month-old EFAD mice. Female APOE4 mice had the highest Aβ deposition, fibrillar amyloid deposits and neuroinflammation as well as earlier behavior deficits. Interestingly, we found that female APOE3 mice and male APOE4 mice had similar levels of pathology. Collectively our data support that the combination of APOE4 and female sex is the most detrimental combination for AD, and that at older ages, female sex may be equivalent to APOE4 genotype.